Beckman pH 4, 7 & 10 Buffer Solutions - Beckman Instruments Photographic Services Section (1969)
The three pH buffer solutions were color-coded Red (pH 4), Green (pH 7), and Blue (pH 10).
Keywords: Hydrogen-ion concentration--Measurement; Buffer solutions; Beckman Instruments, Inc.